Hydrothermal decarboxylation of unsaturated fatty acids over PtSnx/C catalysts. (15th September 2015) - Yeh, Thomas M.; Hockstad, Ryan L.; Linic, Suljo; Savage, Phillip E.
Highlights: Pt3 Sn/C shows higher selectivity for decarboxylation of stearic acid than Pt/C. Pt3 Sn/C shows 3/2× the selectivity for decarboxylation of oleic/linoleic acid. Labeled water experiments show steam reforming to provide hydrogen. Higher Sn loadings led to better carbon recoveries for linoleic acid. Abstract: Decarboxylation of fatty acids is a path to fuel-range hydrocarbons from renewable plant and seed oils. Pt/C is an effective hydrothermal catalyst for decarboxylating saturated fatty acids without added hydrogen, but it has shown low selectivity and activity for decarboxylating unsaturated fatty acids, which are prevalent in plant oils from soy and algae. To develop better decarboxylation catalysts, we compared three different Sn containing alloys, Pt3 Sn/C, PtSn/C, and PtSn3 /C, to Pt/C by performing batch reactions in liquid water at 350 °C for two hours with stearic (C18:0), oleic (C18:1), and linoleic (C18:2) acids. Pt/C gave yields of 0.70 ± 0.05, 0.16 ± 0.03, and 0.083 ± 0.009 for the C17 alkane, but none of the direct decarboxylation products (i.e., C17 alkenes), for the oleic and linoleic acid feeds. Stearic acid was the major byproduct from the unsaturated fatty acids. In contrast, the PtSn x /C catalysts provided two to three times higher C17 alkane yields at identical conditions. Experiments in D2 O showed that water molecules were a source of hydrogen for saturation of the fatty acids. These results show that PtSn x alloys give better performance than Pt alone for the hydrothermal conversion of renewable fatty acids to fuel range hydrocarbons.